THE ROLE OF THE PRIVATE LEADERSHIP IN IMPROVING THE QUALITY OF EDUCATION IN GALIH AGUNG PRIVATE HIGH SCHOOL KUTALIMBARU - Nur Sya'adah Br Ginting; Mardianto Mardianto; Yusuf Hadijaya (Research and Development Journal of Education, 2023)
The purpose of this research is to determine the roles of leadership, efforts, and obstacles faced by the school principal in enhancing the competency standards of graduates at Galih Agung Private High School, Kutalimbaru. The method used in this research is qualitative research with a descriptive approach. The research location is at Galih Agung Private High School, Kutalimbaru. The primary data sources for this research are the School Principal, the Vice Principal of Curriculum, the Vice Principal of Facilities and Infrastructure, and the teachers at Galih Agung Private High School, Kutalimbaru. Data collection techniques include observation, interviews, and documentation. The data analysis technique involves data reduction, data presentation, drawing conclusions, and examination of data validity using credibility, transferability, dependability, and confirmability. The research findings indicate that: 1) The role of the school principal's leadership in enhancing the graduates' competency at Galih Agung Private High School is demonstrated by setting a good example for educators, educational staff, and students. 2) The efforts made by the school principal in improving the graduates' competency at Galih Agung Private High School have been effective by collaborating with other campuses, consulting with psychologists, and planning special class programs. 3) The obstacles in improving the quality of education at Galih Agung Private High School include a lack of cooperation between parents and the school, where some parents are not very supportive of their children's abilities.